2019
DOI: 10.1016/j.jecp.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Object complexity modulates the association between action and perception in childhood

Abstract: Vision-for-action and vision-for-perception both rely on shape representations derived within the visual system. Whether the same psychological and neural mechanisms underlie both forms of behavior remain hotly contested and whether this arrangement is equivalent in adults and children is controversial, as well. To address these outstanding questions, we utilized an established psychophysical heuristic, Weber's law, which, in adults, has typically been observed for perceptual judgment tasks but not for actions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
(73 reference statements)
2
10
0
Order By: Relevance
“…Such findings confirm that there is early sensitivity of this region to object shape (Emberson et al, 2017), but that the underlying neural representations are still subject to a protracted developmental trajectory. This conclusion is also consistent with behavioral observations that have documented reduced sensitivity to object structural information and spatial organization in children (Freud, Culham, Namdar, & Behrmann, 2019;Kovács, Kozma, Fehér, & Benedek, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…Such findings confirm that there is early sensitivity of this region to object shape (Emberson et al, 2017), but that the underlying neural representations are still subject to a protracted developmental trajectory. This conclusion is also consistent with behavioral observations that have documented reduced sensitivity to object structural information and spatial organization in children (Freud, Culham, Namdar, & Behrmann, 2019;Kovács, Kozma, Fehér, & Benedek, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…Our results, collectively, support an input-driven model of white matter development ( Figure 1 ) and suggest that the PVP might facilitate interactions between dorsal and ventral visual streams during development (14,15) . We first demonstrated that the difference between child and adult microstructure increased linearly from early to late pathways: VOF, VHP, PVP, DHP, FAT ( Figure 3 ).…”
Section: Slf3)supporting
confidence: 82%
“…A large body of work has demonstrated a degree of functional segregation between perceptual processing associated with the ventral stream and action processing associated with the dorsal stream (1,2,6,(8)(9)(10)(11) . However, these two streams do interact (5,7,12,13) and a handful of studies suggest that the two streams interact differently in childhood than in adulthood (14,15) .…”
Section: Introductionmentioning
confidence: 99%
“…Then we averaged all trials within each condition to show group-level velocity and aperture profile in absolute time (in seconds). We additionally sampled the velocity and aperture size at each normalized time point (Freud, Culham, Namdar, & Behrmann, 2019;Freud & Ganel, 2015;Ganel et al, 2012) to plot the velocity profile of the hand and foot at an aligned time scale.…”
Section: Discussionmentioning
confidence: 99%